Burkholderia thailandensis as a Model System for the Study of the Virulence-Associated Type III Secretion System of Burkholderia pseudomallei - Haraga, Andrea (American Society for Microbiology (ASM), 2008)
Burkholderia pseudomallei is a bacterial pathogen that causes a broad spectrum of clinical symptoms collectively known as melioidosis. Since it can be acquired by inhalation and is difficult to eradicate due to its resistance to a wide group of antibiotics and capacity for latency, work with B. pseudomallei requires a biosafety level 3 (BSL-3) containment facility. The bsa (Burkholderia secretion apparatus)-encoded type III secretion system (TTSS) has been shown to be required for its full virulence in a number of animal models. TTSSs are export devices found in a variety of gram-negative bacteria that translocate bacterial effector proteins across host cell membranes into the cytoplasm of host cells. Although the Bsa TTSS has been shown to play an important role in the ability of B. pseudomallei to survive and replicate in mammalian cells, escape from the endocytic vacuole, and spread from cell to cell, little is known about its effectors mediating these functions. Using bioinformatics, we identified homologs of several known TTSS effectors from other bacteria in the B. pseudomallei genome. In addition, we show that orthologs of these putative effectors exist in the genome of B. thailandensis, a closely related bacterium that is rarely pathogenic to humans. By generating a Bsa TTSS mutant B. thailandensis strain, we also demonstrated that the Bsa TTSS has similar functions in the two species. Therefore, we propose B. thailandensis as a useful BSL-1 model system to study the role of the Bsa TTSS during Burkholderia infection of mammalian cells and animals.